Inhibition of Germ Tube Formation in Mucor & Candida by JRK’s DCOD - G.V., Amruthavalli; R., Gayathri (RA Journal of Applied Research, 2021)
JRK’s DOCD is a proprietary siddha medicine, indicated for prevention of co-morbidities of diabetes. Earlier studies on the product has proven its effect in boosting the phagocyte mediated immunity. In the current study the ability of the product in preventing pathogenicity of fungi is evaluated. Germ tube formation is proven to increase the pathogenicity of the fungi than the spores alone. For this different species of fungi i.e., Candida albicans, 2 isolates of Candida dubelensis and three isolates of Mucor and 1 isolate of Rhizopus are taken. These fungal cultures when treated with the JRK’s DCOD, there is an inhibition of germ tube formation compared to control. Complete study details are presented in the paper.